Effect of mangrove leaf litter on shrimp (Penaeus monodon, Fabricius, 1798) growth and color - Md. Iftakharul Alam; Sanjida Yeasmin; Mst. Muslima Khatun; Md. Moshiur Rahman; Moin Uddin Ahmed; Adolphe O. Debrot; Md. Nazmul Ahsan; M.C.J. Verdegem (Aquaculture Reports, 2022)
Color, texture and flavor are all important determinants of seafood product quality and value. For shrimp, Penaeus monodon, one of the highest-priced shrimp species of the South-East Asia shrimp industry, dark tiger-striped coloration is a key product quality criterion. We evaluated the effects of leaf litter of the mangrove species Avicennia officinalis (AO), Heritiera fomes (HF), Sonneratia apetala (SA) and S.caseolaris (SC) on length, weight and body color of shrimp (Penaeus monodon) post-larvae (PL). Fifteen-day-old PL (weight: 0.01 g) were reared in 1100-L fiber-reinforced polyethylene tanks. Five treatments having three replications were conducted for four weeks. Four treatments received leaf litter of the four mangrove species and supplemental feeds and one control treatment was provided with supplemental feed only (FO). The pH, biological oxygen demand (BOD5), chemical oxygen demand (COD) and phytoplankton and zooplankton biomass were lower, while total ammonia nitrogen (TAN) concentration were significantly higher in the FO treatment than in treatments including leaf litter. PL survival averaged 89% and only differed significantly between the SA and SC leaf litter treatments (p < 0.05). After 4 weeks of culture, larvae in the FO treatment had significantly shorter body and carapace length, lower body weight and a lower specific growth rate than larvae in the other treatments, while SA-reared larvae attained significantly greater length and weight than in the other leaf litter treatments. Shrimp body coloration and pattern with leaf litter treatments were significantly different from the FO treatment. SA-reared larvae at harvest were significantly darker in body color than larvae reared with other mangrove species. Shrimp value chain stakeholders preferred dark shrimp as an indicator of organic production and higher price. Mangrove leaf litter was found to enhance the production and color quality of black tiger shrimp and this technique can be applied in commercial shrimp aquaculture.